SELF CARE DAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Errick Endra Cita; isti antari (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Background : International Diabetes Federation (IDF) said that Indonesia have high percetage of diabetes mellitus type2, and placed Indonesia on the sixth of he ten countries. Purpose : To find out the relationship between self-care and blood sugar level of patient with type 2 diabetes mellitus in Hospital. Method : The design of this research is correlational by using cross sectional approach. The sampling technique is non probability sampling using consecutive sampling technique with 51 respondents. The self-care data was taken using SDSCA (The Summary of Diabetes Self-care Activity) questionnaire. Result :There is a significant correlation between self care with when blood sugar level of type 2 diabetes mellitus patient with p value of 0.000 and very strong relationship tensile with correlation coefficient value of -0.969 and the direction of negative relationship which means lower self care then the higher when blood sugar levels of patients with type 2 diabetes mellitus. Conclusion : There is a signifcant correlation between self care and blood sugar levels of patients with type 2 diabetes mellitus in Hospital. The lowe self care then the higher blood sugar levels.